COVID-19 Pandemic Impact on Employees’ Physical Activity - Ráthonyi, Gergely; Bácsné Bába, Éva; Szabados, György; Ráthonyi-Ódor, Kinga (International Journal of Engineering and Management Sciences, 2021)
Globalization and the recent explosive development of technology have significantly changed people’s lifestyles resulting in an increase in the number of people living a sedentary lifestyle. COVID-19 pandemic has exacerbated the situation and created an unprecedented situation in the world. In the present study, we investigate changes in the physical activity and sedentary behavior of adult workers caused by the coronavirus epidemic. In our online cross-sectional research, we used snowball methodology. The target group of the survey was adult workers. 108 people filled in the questionnaire, the majority (73.1%) are women, the average age is 37.18 years and most of them have higher degrees (Diploma: 74%, PhD: 14%). The present study revealed a decrease in physical activity and an increase in sedentary time for the employees in our study. Despite respondents detected a decrease in their physical activity, an increase was reported in the proportion of online training participants. The majority of respondents partially, or totally switched to work from home during the pandemic, which may further increase their sedentary lifestyle. We did not find significant differences among the domain of work and leisure time or occupational physical activity patterns. The workplace is a great opportunity for promoting physical activity and reducing sedentary time in the adult working population, therefore it would be important for organizations, decision-makers and health professionals to work on the design of strategies to these goals.